Dopamine internalization via Uptake2 and stimulation of intracellular D5-receptor-dependent calcium mobilization and CDP-diacylglycerol signaling - Kang, Wenfei; Siewe, Arlette Deukam; Oluigbo, Chizurum C.; Arijesudade, Mercy O.; Brailoiu, Eugen; Undieh, Ashiwel S. (Frontiers in Pharmacology, 2024)
Dopamine stimulates CDP-diacylglycerol biosynthesis through D1-like receptors, particularly the D5 subtype most of which is intracellularly localized. CDP-diacylglycerol regulates phosphatidylinositol-4,5-bisphosphate-dependent signaling cascades by serving as obligatory substrate for phosphatidylinositol biosynthesis. Here, we used acute and organotypic brain tissues and cultured cells to explore the mechanism by which extracellular dopamine acts to modulate intracellular CDP-diacylglycerol. Dopamine stimulated CDP-diacylglycerol in organotypic and neural cells lacking the presynaptic dopamine transporter, and this action was selectively mimicked by D1-like receptor agonists SKF38393 and SKF83959. Dopaminergic CDP-diacylglycerol stimulation was blocked by decynium-22 which blocks Uptake2-like transporters and by antimicrotubule disrupters of cytoskeletal transport, suggesting transmembrane uptake and guided transport of the ligands to intracellular sites of CDP-diacylglycerol regulation. Fluorescent or radiolabeled dopamine was saturably transported into primary neurons or B35 neuroblastoma cells expressing the plasmamembrane monoamine transporter, PMAT. Microinjection of ten-nanomolar final concentration of dopamine into human D5-receptor-transfected U2-OS cells rapidly and transiently increased cytosolic calcium concentrations by 316%, whereas non-D5-receptor-expressing U2-OS cells showed no response. Given that U2-OS cells natively express PMAT, bath application of ten micromolar dopamine slowly increased cytosolic calcium in D5-expressing cells. These observations indicate that dopamine is actively transported by a PMAT-implicated Uptake2-like mechanism into postsynaptic-type dopaminoceptive cells where the monoamine stimulates its intracellular D5-type receptors to mobilize cytosolic calcium and promote CDP-diacylglycerol biosynthesis. This is probably the first demonstration of functional intracellular dopamine receptor coupling in neural tissue, thus challenging the conventional paradigm that postsynaptic dopamine uptake serves merely as a mechanism for deactivating spent or excessive synaptic transmitter.